Effect of energy input on microstructural features and mechanical properties of medium chromium ferritic stainless steel welds - Amuda, Muhammed Olawale Hakeem; Mridha, Shahjahan (2011)
Medium chromium ferritic stainless steel conforming to AISI 430 was TIG-welded with different energy input 205J/mm ≤ HI ≤ 2304J/mm in argon shielding environment and characterized for microstructural features as well as mechanical properties. Macro profiling of the weld section show large distortion with wider HAZ as the energy input increases. The optical microscopy and XRD characterization of the weld section revealed the presence of high temperature delta ferrite (71%), martensite (19%) and intergranular carbide precipitates (10%). Grain growth in the weld section can be up to 16 times the grain size of the base metal while the grain structure changed from columnar grains to equiaxed grains as the welding speed increases particularly between 2.5 and 3.5mm/s. The loss in mechanical property in the weld section is 20-56% of the base metal though the loss is more pronounced in welds made with energy input greater than 1576J/mm. This level of loss is an improvement over the published values for GTA welded ferritic stainless steel. The fractograph of the weld show different failure modes of dimple and cleavage fracture depending on the energy input. The present work has shown that using an energy input rate greater than 1576J/mm during GTA welding of medium chromium ferritic stainless steel severely reduces the weld section strength and encourages cleavage fracture.